Performance of bentonite and zeolite mixtures as grounding enhancement materials - Wan Ahmad, W. F. H.; Marudin, N.; Jasni, J.; Ab-Kadir, M. Z. A. (IEEE, 2023)
Grounding system is essential in order to provide protection and to reduce the risk of severe electrical shock to the personnel as well as power system equipment during both normal and fault operation. A properly secured grounding system will enable the fault current to be dispersed to earth at the shortest time possible. Therefore, it is important to have a good grounding system in both normal and fault conditions, and one way to achieve that is by adding NEMs to treat its surrounding soil, where Bentonite and Zeolite were considered in this study. These two NEMs were mixed with water and their performances were compared to a Reference grounding system where there is no NEM installed in the vicinity of the ground conductor. The performance of such grounding systems were measured by the percentage reduction of their earth resistances, which were measured daily for 150 days, i.e. from 19th December 2016 till 18th May 2017 where Fall-of-Potential technique was employed. Note that in this work, it has found that the best grounding system in the descending order were Bentonite 100%, Bentonite and Zeolite Mix A, Bentonite and Zeolite Mix B, Zeolite 100% and References grounding systems. However, being Mix A was having a slightly better performance compared to its counterpart Mix B, it would be interesting to further engage with various mixtures of Bentonite and Zeolite as grounding enhancement materials for future works. Note that Bentonite ratio was more in Mix A compared to Mix B.